A rare case of congenital cystic adenomatoid malformation: Mimics pneumonia manifestations. (June 2021) - Badour, Maysaa; Hussain, Bara'a; Hammed, Ali; Sawssan ali,; falyon, Saeed
Abstract: Introduction and importance: Congenital cystic adenomatoid malformation (CCAM) is a rare malformation, with unknown causes, that affects distal bronchi. It accounts for 25% of congenital pulmonary malformation s and most cases are found in neonates and babies. The mortality rate of prenatally diagnosed cases ranges from 9 to 49%. The risk factors for poor outcome include hydropsfoetalis, microcystic CCAM and the overall size of the lesions. The mainstay of CCAM treatment is surgical excision that prevents complications such as recurrent infections, pneumothorax and malignancy. Case presentation: Our case is a 4-month-old boy born presented with shortness of breath and poor suckling. He was admitted to intensive care for respiratory distress. Clinical discussion: A working diagnosis of pneumonia was entertained and the patient given humidified oxygen through nasal prongs, intravenous fluids and antibiotics. Thoracic CT showed a cystic malformation in the left lower lung lobe. Due to continuing recurrent infections and the risk of rupturing of the cyst with subsequent pneumothorax, it was decided to proceed with a left lower lobectomy. The post-operative course was uneventful and the patient was discharged home on the fifth post-operative day. Conclusion: Congenital cystic adenomatoid malformation should be a differential diagnosis of pneumonia. A real awareness of this rare entity among pediatricians and radiologists should allow early diagnosis and proper treatment. Highlights: Congenital cystic adenomatoid malformation (CCAM) is a rare malformation, with unknown causes, that affects distal bronchi. Congenital cystic adenomatoid malformation should be a differential diagnosis of pneumonia. A real awareness of this rare entity should allow early diagnosis and proper treatment.